MULTICULTURAL EDUCATION AND THE NATIONALISTIC REALITY (PHOTOGRAPH THE ROLE OF TEACHERS IN BUILDING A MULTICULTURAL AWARENESS IN INDONESIA) - Ulfa Masamah (Qudus International Journal of Islamic Studies, 2016)
Various multidimensional crises that exist in Indonesia which is recognized or not is the part of cultural problem, one of the reasons is the diversity of the cultures that exist in our society. The diversity of culture should not be the cause of the existence of discrimination, injustice, suspicion and a variety of human rights violations, but being the power to build a community sense. The multiculturalism thought that exists in Indonesia resting on Islam as a source of thought. With the implementation of multicultural education, teachers are expected to be able to encourage learners to have an awareness and understanding to always uphold the values of justice, democracy, humanity and pluralism in the association in the middle of the national reality that is full of diversity.